Pemasaran Media Sosial Produk Kelompok Wanita Tani Desa Sungai Langka - Roslina Roslina; Habibullah Jimad; Nova Mardiana (Yumary: Jurnal Pengabdian kepada Masyarakat, 2023)
Purpose: The purpose of this activity is to empower women farmer groups to be independent of by increasing their knowledge of and skills  in using social media to market their products. Methodology/approach: Community service activities are carried out for women farmer groups in Sungai Langka Village, Pesawaran using several methods, including lectures and discussions; training in the form of practicing Instagram account creation; mentoring; and evaluation. Results/findings: The activities carried out by the service team were able to provide benefits for the participants. This can be seen from the testimonies given by the participants. The activity also succeeded in making farmer groups create Instagram accounts for business activities that were separated from personal Instagram accounts to make it easier to manage. Monitoring and evaluation are carried out for participants who encounter obstacles in making and marketing their products through Instagram. Conclusion: This activity is expected to be sustainable in order to increase the independence and welfare of women farmers in the Sungai Langka village of Pesawaran, so that they are financially independent and not dependent on others.